ANALISIS KINERJA SEKSI KEAMANAN DAN KETERTIBAN PADA DETENI DI RUMAH DETENSI IMIGRASI (RUDENIM) KOTA PEKANBARU - Syarsabilah Syarsabilah; Hendry Andry (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
ABSTRACT Immigration is a traffic case record people entering or leaving Indonesian territory and monitoring in order to preserve the country's sovereignty. Various factors cause a lot of people doing these activities, some of which protect against the wars in their country, to seek work in another country, to get a more decent life. But in fact, violations in immigration activities such as the absence of travel documents for illegal immigrants. This is of course a negative impact on the country occupied by these immigrants, so the government established the detention center on immigration. it called Rumah Detensi Imigrasi (RUDENIM) is an operation unit that performs the function of the immigration of temporary shelters for foreigners who are subject to administrative immigration measures. People wholiving in Rudenim called deteni. This study to analyze how the performance Seurity and Order Section for Deteni in Rumah Detensi Imigrasi (RUDENIM) Pekanbaru City. In this perfomance study uses some indicator like productivity, responsiveness, responsibility and accountability of the security and order section. The population in this study is the Leader of Rudenim, head of the Security and Order Section, the head of security section, head of order section, Immigration commander, security personnel and Deteni. Next, the entire population were sampled where the head is Rudenim as key informants, as well as the security section and order by using the purposive sampling technique. Then for deteni by insendental sampling techniques. Data collection was conducted by interviews, collection of data from respondents with quisioner, documentation and observation writers to see how the performance of security and order section for deteni Rudenim in Pekanbaru, pesentase analysis uses data to know what percentage of respondents who answered good, enough and less. So, we can conclude that Performance Analysis of Security and Order section of Rumah Detensi Imigrasi for Deteni in Pekanbaru City that are in the category of "enough", according to respondents and observations writer.